2022
DOI: 10.5435/jaaosglobal-d-21-00200
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Surgical Time, Short-term Adverse Events, and Implant Placement Accuracy Between Manual, Robotic-assisted, and Computer-navigated Total Hip Arthroplasty: A Network Meta-analysis of Randomized Controlled Trials

Abstract: Introduction: Recent years have observed the increasing utilization of robotic-assisted and computer navigation techniques in total hip arthroplasty (THA), given the proposed benefits of enhanced consistency and precision in implant placement. The purpose of this study was to conduct a systematic review of randomized controlled trials (RCTs) to determine whether differences in surgical times, adverse events, and implant positioning existed between manual, robotic-assisted, and computer navigation THA. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 45 publications
(49 reference statements)
2
19
0
Order By: Relevance
“…The chatbot correctly identified the typical duration of a THA procedure as well as the possible variance as a result of surgical techniques [5][6][7][8][9] , surgeon experience [10][11][12][13][14] , and patient characteristics. For instance, operative time is significantly affected by patient body mass index [13][14][15][16] .…”
Section: Analysis: Unsatisfactory Requiring Substantial Clarificationmentioning
confidence: 99%
“…The chatbot correctly identified the typical duration of a THA procedure as well as the possible variance as a result of surgical techniques [5][6][7][8][9] , surgeon experience [10][11][12][13][14] , and patient characteristics. For instance, operative time is significantly affected by patient body mass index [13][14][15][16] .…”
Section: Analysis: Unsatisfactory Requiring Substantial Clarificationmentioning
confidence: 99%
“…Interestingly robotic surgeries are longer and require a steeper learning curve (Royal College of Surgeons 2018). In orthopedics and spine surgery, in particular, the use of surgical robots has increased the accuracy of placement of knee and hip prosthesis and osteosynthesis screws into defined "safe zones" (Kunze et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly robotic surgeries are longer and require a steeper learning curve (Royal College of Surgeons 2018). In orthopedics and spine surgery, in particular, the use of surgical robots has increased the accuracy of placement of knee and hip prosthesis and osteosynthesis screws into defined “safe zones” (Kunze et al, 2022). Capturing the benefits in terms of increased longevity of the prosthesis or decreased need for revision surgery, however, has been an elusive goal (Kumar et al, 2021; Nogalo et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of current RA‐THA systems rely on pre‐operative computed tomography (CT) imaging and intraoperative navigation tracker pins to guide the robotic platform, which can prolong pre‐operative and intra‐operative workflows 3,19,20 . However, novel fluoroscopy‐based robotic platforms aim to address these issues through the replacement of pre‐operative CT imaging with the integration of intraoperative fluoroscopy, which removes the need for additional pre‐operative imaging and intraoperative surgical pin placement 3 .…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] The majority of current RA-THA systems rely on pre-operative computed tomography (CT) imaging and intraoperative navigation tracker pins to guide the robotic platform, which can prolong preoperative and intra-operative workflows. 3,19,20 However, novel fluoroscopy-based robotic platforms aim to address these issues through the replacement of pre-operative CT imaging with the integration of intraoperative fluoroscopy, which removes the need for additional pre-operative imaging and intraoperative surgical pin placement. 3 While a cadaveric study has shown improved accuracy of acetabular cup placement with a fluoroscopy-based robotic platform compared to an unassisted approach, 3 no group has examined this novel fluoroscopy-based RA-THA system in clinical practice.…”
Section: Introductionmentioning
confidence: 99%